Correlation between pulmonary vascular performance and hemodynamics in patients with pulmonary arterial hypertension. (31st December 2023) - Yasenjiang, Maimaiti; Cheng, Hui; Guo, Zitong; Yu, Xiaolin; Adilijiang, Tuohuti; Li, Guoqing
ABSTRACT: Objective: To explore the correlation between pulmonary vascular performance and hemodynamics in patients with pulmonary arterial hypertension (PAH), using right heart catheterization (RHC) and intravascular ultrasound (IVUS). Method: A total of 60 patients underwent RHC and IVUS examinations. Of these, 27 patients were diagnosed with PAH associated with connective tissue diseases (PAH-CTD group), 18 patients were diagnosed with other types of PAH (other-types-PAH group), and 15 patients were without PAH (control group). The hemodynamics and morphological parameters of pulmonary vessels in PAH patients were assessed using RHC and IVUS. Results: There were statistically significant differences in right atrial pressure (RAP), pulmonary artery systolic pressure (sPAP), pulmonary artery diastolic pressure (dPAP), mean pulmonary artery pressure (mPAP) and pulmonary vascular resistance (PVR) values between the PAH-CTD group, other-types-PAH group, and the control group (P < .05). No statistically significant difference was noticed in pulmonary artery wedge pressure (PAWP) and cardiac output (CO) values between these three groups (P > .05). The mean wall thickness (MWT), wall thickness percentage (WTP), pulmonary vascular compliance, dilation, elasticity modulus, stiffness index β, and other indicators were significantly different between these three groups (P < .05). Pairwise comparison showed that the average levels of pulmonary vascular compliance and dilation in PAH-CTD group and other-types-PAH group were lower than those in control group, while the average levels of elastic modulus and stiffness index β were higher than those in control group. Conclusion: Pulmonary vascular performance deteriorates in PAH patients, and the performance is better in PAH-CTD patients than in other types of PAH.